Effect of Cerium, Cobalt and Nickel Contaminants on the Oxygen Reduction Reaction at Platinum Electrodes. (24th August 2017) - Dumont, Joseph H; Baker, Andrew M.; Maurya, Sandip; Kim, Yu Seung; Mukundan, Rangachary; Myers, Deborah J; Borup, Rod L.
Abstract : State of the art proton exchange membrane fuel cells contain metallic cations as alloyed Pt catalysts or as additives to improve the chemical stability of membranes. While these novel materials have improved the performance and durability, they can leach out contaminants such as Ce, Ni and Co ions into the ionomer, impact the potency of the additive, decrease the ionomer conductivity and reduce fuel cell performance. We report here that in presence of Ce, Ni and Co, the ionomer conductivity (Nafion 211) decreases by a factor of ~3 with 5.2-19.2 mgmetal cm -3 at 80°C, 100% RH. This performance correlates with a decrease in ORR performance, most notably lower limiting currents 1.1x10 -1 mA cm -2 in proton form vs. 6.2-8.2x10 -2 mA cm 2 with 6-12 mgmetal cm -3 and lower ORR onset potentials at 25°C, 100% RH.